EVALUATION OF COAL DISTRIBUTION FOR ALTERNATIVE ENERGY USING SEISMIC SPECTRAL DECOMPOSITION - Praditiyo Riyadi (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2022)
Indonesia is the largest coal producer in the world, and Sumatera is one of the contributors to Indonesia's coal production. Coal is generally widely used for industrial fuel or power plants with production directly on the surface. The technology to develop coal into alternative energy sources (Coal Bed Methane (CBM) & Underground Coal Gasification (UCG)) began to develop with various production methods in the earth without having to be exploited directly. To apply this production method, it is necessary to analyze the distribution of coal below the earth's surface. The research area is located in the South Sumatera Basin with coal targets in the Muara Enim Formation. The data consists of 3D seismic data and well data as validation. From the well data, it was identified that there was coal in two zones, with an average thickness in Zone A reaching 6 meters while in Zone B the average thickness reaching 11 meters. The results of the amplitude spectrum analysis from the seismic data, obtained three dominant frequency trends from seismic data, 26 Hz, 42 Hz, and 58 Hz. By using the calculation of ¼ wavelength, the frequency that matches the thickness of the coal is 58 Hz for Zone A and 42 Hz for Zone B coal layer. Seismic amplitudes are then separated based on their frequency using the Spectral Decomposition method, and the distribution of coal is validated with existing well data.